TREND CIVITAS AKADEMIKA UIN SUNAN KALIJAGA DALAM MEMBAYAR ZAKAT - Zulkipli Lessy (Al-Maslahah : Jurnal Ilmu Syariah, 2016)
Empowerment of the poor is a long run program. Modern zakat institution is one of the zakat managements to have long run programs than the mosque takmir. As academicians, lectures and professors at UIN Sunan Kalijaga knew the existence and performance of modern zakat management. The research was aimed to explore zakat payment trends conducted by the lecturers and professors. First, the attitude of those lecturers and professors in giving their zakat either fitrah or maal; whether the payment was done by giving direct cash to zakat institutions or to mustahiq and the mosque takmir. Second, reasons that lay beyond choosing the payment methods. The results indicated the respondents tended to conserve the traditional method in giving zakat to the poor and the mosque. From 95 respondents surveyed, fifty five respondents paid their zakat fitrah and maal directly to individuals because they witness living poor individuals in their neighboorhood, and fourty respondents chose the modern method. And, from 95 respondents, twelve of the did not trust zakat institutions. Therefore, they paid their zakat directly to the poor. Keywords: Trend, zakat, institution, mosque, individual. Kata-kata kunci: trend, zakat, lembaga, masjid, individu